Labor Migration, Capital Accumulation, and the Structure of Rural Labor Markets - Dinkelman, Taryn; Kumchulesi, Grace; Mariotti, Martine (The Review of Economics and Statistics, 2024)
Between 1967 and 1974, a bilateral treaty increased circular labor migration from Malawi to South Africa by 200%, bringing over 53 million USD in earnings into origin communities. A deadly migrant worker plane crash in 1974 ended these flows and led to migrant repatriation. We study how this shock affected local labor markets. In regions receiving more migrant capital after the crash, workers, particularly women, shifted from farming into non-farm work over thirty years. Investments in non-farm physical and human capital contribute to these sectoral changes. This natural experiment shows that temporary capital inflows can permanently reshape rural labor markets.